Assessing the Entrepreneurial Attitude (EA) among Graduates and Post Graduate Students of Dhanagdhi City - Adhikari, Tek Bahadur (BMC Research Journal, 2026)
Entrepreneurship education is widely recognized as a pivotal mechanism to enhance employability, stimulate innovation, and foster economic development among graduates. This study aims to investigates the determinants of Entrepreneurial Personal Attitude (EPA) with a focus onthe roles of Entrepreneurial Orientation (EO), University/Campus Environment (UCE), and Socio-Economic Factors (SEF) as a mediating variable among graduating and postgraduate students of Higher Education Institutions (HEIs) in Dhangadhi, Nepal. Based on the Theory of Planned Behavior (TPB), a positivist and deductive research approach was employed. Primary data were collected using five points likert scale structured questionnaire from 346 recent management graduates. The results were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that UCE exerts a significant direct influence on EPA and an even stronger indirect influence through SEF. EO, although not directly associated with EPA, was found to significantly influence SEF, which in turn shaped EPA. Importantly, traditional socio-demographic characteristics such as gender, family income, and parental occupation were not significant predictors. These results demonstrate that HEIs entrepreneurial environments and socio-economic perceptions play a greater role in fostering EPA than demographic backgrounds. This study contributes to the entrepreneurship literature by clarifying the mechanisms through which HEIs and perceived socio-economic conditions shape entrepreneurial attitudes of graduates. The implications highlight the need for universities to design supportive pedagogies, orientation programs, and entrepreneurial ecosystems that not only impart knowledge but also enhance students’ socio-economic confidence. Strengthening these factors can serve as a catalyst for nurturing future entrepreneurs and addressing graduate unemployment challenges in developing economies.